Mayo Clinic Guide to Your Baby's First Years - Cook, Walter J.; Klaas, Kelsey M.; Mayo Clinic (Rochester, MN : Mayo Clinic Press, 2020)
"A complete guide with practical information and support for parents of children from newborn to three years old, by childcare experts at the renowned Mayo Clinic. Written by doctors who are also parents." -- amazon.com.
Caring for your child. Welcome to parenthood! ; Baby's first days ; Feeding your baby ; To solid foods and beyond ; Diapers and all that stuff ; Toilet training ; Bathing and skin care ; Clothing your child ; Sleep and sleep issues ; Comforting a crying baby ; Building a relationship -- Health and safety. Finding the right medical provider ; Checkups ; Vaccinations ; Child care ; Traveling with a little one ; Home and outdoor safety ; Emergency care -- Growth and development -- Common illnesses and concerns -- Managing and enjoying parenthood. Adapting to your new lifestyle ; Parenting as a team ; Single parenting ; Siblings and grandparents ; When to have another child -- Special circumstances. Adoption ; Caring for multiples ; Premature baby ; Delayed development ; Autism spectrum disorder ; Other newborn conditions -- Growth charts: birth to 36 months -- Pain reliever dosage by weight.
Includes index.
"Newborn to age 3." -- cover.
New Book 2022 Fall.
Includes bibliographical references and index.
Keywords: Newborn infants -- Care; Infants -- Care; Toddlers -- Care; Child rearing; Infant, Newborn -- growth & development; Infant Care; Infant Health; Child Rearing; FAMILY & RELATIONSHIPS / Life Stages / Infants & Toddlers; FAMILY & RELATIONSHIPS / Parenting / Motherhood; HEALTH & FITNESS / Children's Health; Toddlers -- Care; Child rearing; Infants -- Care; Newborn infants -- Care; Infants -- Care; Child rearing